DIAGNOSIS AND MANAGEMENT OF ASPERGER SYNDROME - Faizal Minhat; Wayan Westa; Nyoman Ratep (Bali Journal of Medical and Health Sciences, 2013)
Asperger syndrome is the term applied to the mildest and highest functioning end known as the spectrum of pervasive developmental disorders (or the autism spectrum). It is known to be related to a neurologically based disorder of development. Most of the causes of these disorders are unknown, which are deviations or abnormalities in three broad aspects of development: social relatedness and social skills, the use of language for communicative purposes and certain behavioral and stylistic characteristics involving repetitive or perseverative features and a limited but intense range of interests. It is the presence of these three categories of dysfunction, which can range from relatively mild to severe, which clinically defines all of the pervasive developmental disorders, from AS through to classic autism. Some researchers have suggested that the basic neuropsychological deficit is different for the two conditions, but others have been unconvinced that any meaningful distinction can be made between them. Keyword: Asperger Syndrome, Pervasive Developmental Disorders, Autism